Determination of Minimum Enzymatic Decolorization Time of Reactive Dye Solution by Spectroscopic & Mathematical Approach - Celebi, Mithat; Ozdemir, Zafer Omer; Eroglu, Emre; Altikatoglu, Melda; Guney, Ibrahim (OFFICE SPECTROSCOPY & SPECTRAL ANALYSIS, 2015)
Synthetic dyes are very important for textile dyeing, paper printing, color photography and petroleum products. Traditional methods of dye removal include biodegradation, precipitation, adsorption, chemical degradation, photo degradation, and chemical coagulation. Dye decolorization with enzymatic reaction is an important issue for several research field (chemistry, environment) In this study, minimum decolorization time of Remazol Brilliant Blue R dye with Horseradish peroxidase enzyme was calculated using with mathematical equation depending on experimental data. Dye decolorization was determined by monitoring the absorbance decrease at the specific maximum wavelength for dye. All experiments were carried out with different initial dye concentrations of Remazol Brilliant Blue R at 25 degrees C constant temperature for 30 minutes. The development of the least squares estimators for a nonlinear model brings about complications not encountered in the case of the linear model. Decolorization times for completely removal of dye were calculated according to equation. It was shown that mathematical equation was conformed exponential curve for dye degradation.
Keywords: Decolorization; Horseradish peroxidase; Mathematical modeling; Reactive dye; UV-visible spectrophotometry; HORSERADISH-PEROXIDASE; WASTE-WATER; AZO DYES; REMOVAL; OPTIMIZATION; DEGRADATION; REDUCTION; ENZYMES; BLUE; Spectroscopy